Impact of Top Management Decision on Hospital Risk Management: A Scoping Review - Ayu Sekar Melati; Sutopo Patria Jati; Septo Pawelas Arso (GLOBAL HEALTH SCIENCE GROUP, 2025)
Top management decisions play a crucial role in shaping hospital risk management. Effective leadership, resource allocation, and a strong safety culture are essential to minimize risks and improve healthcare quality. This study aims to explore the impact of top management decisions on hospital risk management and to identify key factors that influence the success of patient safety programs. This scoping review followed the PRISMA framework. Articles were systematically searched from PubMed, Scopus, and Google Scholar, focusing on publications from 2005 to 2025. Keywords included hospital risk management, top management, decision making. Ten relevant articles were selected and analyzed thematically to identify key patterns related to leadership decisions in hospital risk management. The study found that top management influences hospital risk management through leadership support, resource allocation, communication, safety culture development, and staff training. However, challenges such as limited resources, inadequate staffing, and underreporting of incidents remain. Top management is crucial in ensuring hospital safety through strong leadership, clear communication, sufficient resources, and ongoing staff training to enhance patient safety and risk management. Overcoming organizational barriers is essential for sustaining long-term safety improvements.